Iqbal’s ideas on man and personality - Abdul Razak, Mohd. Abbas (Research Management Centre, International Islamic University Malaysia, 2013)
Among all creations in the heaven and earth, only man has been bestowed with many distinctive qualities. As the recipient of these distinctive qualities from Allah the Almighty, man is placed on the highest pedestal in the hierarchy of creations. Some of these distinctive features are that man has been created in the best of forms (Al-Qur’ān, Al-Tīn: 1-4), provided with the creative intelligence (Al-Qur’ān, Al-Baqarah: 31-34), given the power of speech and freedom of choice (Al-Qur’ān, Al-Rahmān: 4; Al-Insān: 3). Due to the fact that man has been endowed with such noble qualities or for some other reasons only known to the Creator, man has been chosen to be HisKhalīfah (vicegerent) on earth. Apart from that, man has been further honoured in his stature and position when Allah made all things created in the heaven and earth to be of service to him. (Al-Qur’ān, Al-Jāthiyah: 13; Al-Isrā’:70).This research is an attempt to explore the philosophical ideas of Muhammad Iqbal (1877-1938) with regard to man and personality. Iqbal, who had a strong Islamic background, promoted many positive ideas on man and the latent powers that are within the human psyche. His theory of personality is dynamic in nature that inspires man to sink into his psyche and to bring out all that are positive within him. Iqbal believed that by actualizing the hidden powers within man, he would be able to transform this world into a better place for all to live. This act, in turn, will bring one in close contact with God. On the whole, his theory on personality gives man a dignified position as the vicegerent of God ( Khalīfatullāhfī al-Ard), who is able to create a better world. The findings of this have indicated that Iqbal’s ideas on human nature and personality development are very much in line with the spirit of Islamization of Psychology. Moreover, his ideas on man which are dynamic in nature can yield positive results when applied in the fields of education, motivation, human capital development, leadership training, etc.